REGISTRO DE LA ASOCIACION DEPREDADORA DE ZAGLOBA BEAUMONTI CASEY (COLEOPTERA: COCCINELLIDAE) CON UNASPIS CITRI (COMSTOCK) (HOMOPTERA: DIASPIDIDAE) - Coronado Blanco, Juana María; Ruíz Cancino, Enrique; Marín Jarillo, Antonio (Instituto de Ecología, A.C., 2000)
The predator - prey association of Zagloba beaumonti Casey with the citrus snow scale, Unaspis citrí (Comstock) is registered. Besides, Z. beaumonti is a new record for México.